Design considerations of structurally scalable Unmanned Aerial Vehicles (UAV) - Foo, Faith Inn May (2015)
The purpose of this project is to design a UAV that is scalable, with its configuration being dependent on the payload required. Depending on the payload requirements, the UAV can be configured to utilize a variable number of motors, through a “plug-and-play” system. The two designs described in this report achieve scalability differently. The first design (“Prototype 1”) was based on the concept of utilizing multiple identical multi-rotor UAVs mounted on a platform for scalability. The second design (“Prototype 2”) provided scalability by varying the number of rotors on a single UAV, allowing for scalability to be achieved simply without needing an additional platform. The final design (“Final Design”) was based on Prototype 2, with further improvements made to include the implementation of a “plug-and-play” system. This was a major improvement from conventional systems that required the UAV to be re-programmed for each configuration of variable rotor numbers. The construction of both designs will be discussed in this report.